A Survey Study of Various Software Cost Effort Estimation in Perspective of India - Anooja, A; Qurashi, Jameel Ahmad; Kumar, Sanjay (International Journal of Computer Sciences and Engineering, 2019)
According to Current scenario of India cost estimation plays a vital role in the whole cycle of software development. Software development process involves various techniques and skills which help for accurate estimation, overall charges, early delivery date, required effort and assurance of project acceptance or denial. This paper presents current scenario of knowledge in the field of software development methodologies through conducting systematic survey of cost estimation in Agile Software Development, which will be useful to understand current trends in cost estimation in Agile Software Development stages. Stages are building blocks of any software development methodology which are presented graphically. Software development methodologies are compared by highlighting strengths and weaknesses from the stakeholder’s point of view. This research is related to software cost and effort estimation in software development.